Paracetamol (Acetaminophen) – a Popular and Widely Used Nonopioid Analgesic - Klotz, U. (Arzneimittelforschung, 2012)
For several decades paracetamol has proven its clinical efficacy and safety in the treatment of various acute and chronic pain states. Whereas its pharmacokinetic properties (high oral bioavailability, good penetration into the brain, relative rapid hepatic elimination) are well known, its exact central mode of action remains to be elucidated. According to many international guidelines/recommendations paracetamol is a drug of first choice for relieving mild to moderate pain. It has been successfully combined with opioids for severe pain. Due to its cardiovascular, renal and gastrointestinal safety paracetamol offers several advantages vs. NSAIDs. It should be realized that the maximum daily dose is restricted to 4 g to avoid unnecessary hepatic complications. Keeping this limitation in mind paracetamol still represents a valuable first-line agent in the pharmacological management of pain.
Keywords: paracetamol; acetaminophen; pain management; pharmacological properties; therapeutic use; clinical safety; NSAID